ANALISIS PENDAPATAN KOMPOSISI AGROFORESTRI PETANI DI DESA ROMAREA KECAMATAN NANGAPANDA KABUPATEN ENDE - Maria Minata; Wilhelmina Seran; I Wayan Nampa (Program Studi Kehutanan, Fakultas Pertanian, Universitas Nusa Cendana, 2021)
Agroforestry is a combination of forestry plants with agricultural crops or livestock in one plot of land. Agroforestry systems provide many advantages in terms of economic and social ecology, one of which is providing income for farmers. This income is influenced by the composition of the type of agroforestry. This study aims to determine the composition of farmers' agroforestry, income per composition and the largest income of all compositions. This research was conducted in the village of Romarea, District of Ende. To analyze the largest income composition of the respondents' agroforestry, each composition was grouped, then calculated the income per composition and determined the largest income from all compositions. The results of the research obtained are that there are 19 agroofrestri compositions in Romarea Village, Nangapanda District, Ende Regency. There are 10 compositions that are above the average and 9 compositions that are below the average income. The largest income is in composition 5 with the types of plants planted namely cocoa, vanilla, candlenut, clove, areca nut, lamtoro, gamal and mahogany as well as livestock, namely goat and buffalo.